The Impact of Emotional Intelligence and Conflict Resolution on Employees Well-Being - Mahar, Dr Shoukat Ali; Lashari, Dr Irfan Ahmed; Larik, Dr. Akhlaque Hussain; Channa, Dr Muhammad Asif; Lashari, Ashique Ali (ACADEMIA International Journal for Social Sciences, 2025)
This study examined how emotional intelligence (EI), and conflict management styles influence employee well-being in Pakistani commercial banks. Data was collected from ninety-one bank employees in Khairpur Mir’s, Sindh out of a total of 118 employees. The study analyzed how two EI dimensions (self-awareness, social awareness) and two conflict styles (avoiding, problem-solving) predict employees well-being. Descriptive statistics confirmed that our scales were reliable (Cronbach’s α ranged from .768 to .845). Correlation analysis showed that problem-solving and self-awareness were strongly positively related to well-being, while social awareness showed little relation in simple bivariate tests. In multiple regression, the model was highly significant (F (4,86) =3466.58, p